Impact of Customer Attitude on Customer Loyalty in Beauty Parlour Industry: An Empirical Study - Dr. M. Suresh (International Journal of Advanced Science and Technology, 2020)
This present empirical study was aimed to explore the influence of customer attitude on loyalty of beauty parlour customers in Chennai city. The researcher has adopted survey method and questionnaire method to collect responses from beauty parlour customers residing in Chennai city by using convenience sampling technique. The 160 samples collected were subjected to data analysis using SPSS Version 23.0 and statistical tools such as, percentage analysis, correlation analysis and multiple regression analysis has been applied to draw meaningful solutions to the research objectives. The result indicates that The beauty parlour outlet atmosphere, promotional, responsiveness and functional factors play an imperative role in significantly predicting the customer loyalty in the beauty parlour services. The researchers concluded that the owners should take necessary steps to keep their customers more satisfied. However, the pattern of findings makes a great deal of intuitive sense by providing an assessment of the services.